2022
DOI: 10.3390/app12125978
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Studies of Work Function Changes of CO Adsorption on Clean and Pd-Doped ZnGa2O4(111) Surfaces for Gas Sensors

Abstract: We performed first-principles calculations to study the adsorption of the CO molecules on both clean and Pd-doped ZnGa2O4(111) surfaces. The adsorption reaction and work function of the CO adsorption models were examined. The CO molecules on the clean and Pd-doped ZnGa2O4(111) surfaces exhibit maximum work function changes of −0.55 eV and −0.79 eV, respectively. The work function change of Pd-doped ZnGa2O4(111) for detecting CO is 1.43 times higher than that of the clean ZnGa2O4(111). In addition, the adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Furthermore, the energies of the vacuum level and Fermi level, work function, and work function change in our geometric models are shown in Table1. In our previous studies[37][38][39], the alterations in the work function of CO, NO 2 , and H 2 S molecules upon interaction with the ZnGa 2 O 4 (111) surface align with experimental findings. These changes in the work function signify the overcoming of electron barriers induced by gas adsorption, contributing to the quantitative assessment of gas-sensing characteristics in zinc gallium oxide.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the energies of the vacuum level and Fermi level, work function, and work function change in our geometric models are shown in Table1. In our previous studies[37][38][39], the alterations in the work function of CO, NO 2 , and H 2 S molecules upon interaction with the ZnGa 2 O 4 (111) surface align with experimental findings. These changes in the work function signify the overcoming of electron barriers induced by gas adsorption, contributing to the quantitative assessment of gas-sensing characteristics in zinc gallium oxide.…”
supporting
confidence: 82%
“…Since InAlN is an n -type semiconductor and acetone gas is a reducing gas, a reduction in depletion width layers is favorable upon exposure to reducing gas. In recent studies, we have successfully illustrated the electron flow from the reducing gas to the n -type semiconductor until the Fermi level equilibrium is achieved [ 37 , 38 , 39 ]. This phenomenon leads to the formation of ohmic contact.…”
Section: Resultsmentioning
confidence: 99%
“…The electron can flow from the sheet to the oxidizing-type gas until equilibrium is reached at the Fermi level, causing alteration to the surface energy band, thus increasing the surface resistance and ϕ. On the other hand, for reducing gases, the electron transfer occurs from the gas molecules to the sheet until the Fermi level is balanced, which results in ohmic contact formation . The ohmic contact makes the electrons inside the sheet easily migrate to the surface, thereby reducing the surface resistance and the ϕ of the adsorbed system.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for reducing gases, the electron transfer occurs from the gas molecules to the sheet until the Fermi level is balanced, which results in ohmic contact formation. 56 The ohmic contact makes the electrons inside the sheet easily migrate to the surface, thereby reducing the surface resistance and the ϕ of the adsorbed system. In our case, Bader charge analysis revealed that the charge transfer occurs mostly from Mo 2 CT x to the CWAs.…”
Section: Electrostatic Potential and Work Functionmentioning
confidence: 99%
“…There are many published works on the ab initio studies of adsorption of CO on W(111) and Pt(111), starting with the work if Chen, Scholl and Johnson [1] in 2006 to publications in 2022 by Goonusooria [2] and J. C Tung et al [3].…”
Section: Introductionmentioning
confidence: 99%